Analisis Strategi Fund Raising dalam Penyelenggaraan Program Pendidikan Nonformal pada Pusat Kegiatan Belajar Masyarakat Ceria - Rizka, Muhammad Arief; Hardiansyah, Rila (Universitas Negeri Semarang, 2017)
Implementing of nonformal education program at PKBM didn’t show individual and sustinable yet so it appeared impression inconsistency and less profesionally in management. There were many nonformal education program which were implemented by PKBM had many obstacles in conducting program, and it was regardless from supporting human resources especially funding. The purpose of this research was to analysis fund raising strategy in implementing nonformal education strategy which was conducted by PKBM Ceria. This research used case study method with qualitative approach. The data resources in this research was management, teacher of PKBM Ceria and supervisor of PLS/PNF. Technique of data collection used interview, observation, and documentation. The data analysis used interactive analysis model namely data collection, data reduction, data presentation, and verivication or conclusion drawing. Technique of data validity used resources triangulation. Conclusion of this research was fund raising strategy in implementing PNF program which was conducted by PKBM Ceria used public education strategy, fund service strategy, and competency strategy to central or district goverment institution which had been relevant with implementing of nonformal education.